OPTIMALISASI PERLINDUNGAN HUKUM NASABAH FINANCIAL TECHNOLOGY (FINTECH) BERBASIS PEER TO PEER LENDING PERSPEKTIF TEORI SISTEM HUKUM - Raja Devan Zularham, (2021)
One of the technological developments that is the subject of recent studies in Indonesia is Financial Technology (Fintech). One of the basic forms of fintech is Peer to Peer Landing or startups that provide online platform loans. In contrast to the loan and borrowing agreement for service money regulated in the Criminal Code book which only involves lenders and loan recipients, in Peer to Peer Lending or information technology- based loan recipients, the parties in P2P Lending-based Fintech consist of information technology-based lending providers, lenders and loan recipients. This study aims to determine the protection of financial technology customers based on peer to peer landing according to applicable law in Indonesia. Legal inconsistencies when there are problems creating gray areas, this sometimes even leads to criminalization. So it is important to make an inventory of any legal products that collide with each other.